PROFIL PROSES BERPIKIR KRITIS SISWA KELAS VIII SMP NEGERI 3 SURAKARTA DALAM MEMECAHKAN MASALAH POKOK BAHASAN SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) DITINJAU DARI KECERDASAN MAJEMUK DAN GENDER - Ambarawati, Mika; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aim of this research was to describe the profile of critical thinking process of the students in grade VIII of State Junior Secondary School 3 of Surakarta in solving the problems on linear equation of two variables (LETV) viewed from the multiple intelligence and gender. This research used the descriptive research method with the qualitative explorative approach. The subjects of the research were taken by using the purposive sampling technique. The subjects of the research were four students in Grade VIII of State Junior Secondary School 3 of Surakarta, one male student and female student with linguistic intelligence, and one male student and one female student with mathematical-logical intelligence. The instruments used to gather the data of the research were multiple intelligence questionnaire, worksheet for mathematical problem-solving, and interview guidelines. The data were collected through questionnaire and task-based interview on the learning material of LETV. They were validated by using the time triangulation and the reference fulfillment. The data were analyzed using a Miles and Huberman?s concept, that was data reduction, presentation, and conclusion. The results of the research are as follows. 1) The male  and female students with linguistic intelligence had a good ability to capture information and may communicate it effectively both written and orally. The critical thinking can be realized through four phases. However,  the male in the recognition phase, they encounters a difficulty i.e. the question they mentions is less complete.  In addition, in thinking about alternatives, they are only able to mention one problem-solving alternative, namely: mixed alternative. 2) The male and female students with mathematical-logical intelligence are able to think logically. They are able to do categorization, classification, conclusion drawing over a problem. The  critical thinking can be realized through four phases. However, in the recognition phase, they encounters a difficulty i.e. the question they mentions is less complete.  In addition, in thinking about alternatives, they are only able to mention two problem-solving alternatives, namely: mixed alternative and substitution alternative.Keywords: profile of the process of critical thinking, problem solving, multiple intelligence, and gender.